The peroxynitrite catalyst WW-85 improves microcirculation in ovine smoke inhalation injury and septic shock - Maybauer, Dirk M. (2011)
This prospective, randomized, controlled experimental study looks at the effects of the peroxynitrite decomposition catalyst WW-85 on global hemodynamics and regional microvascular blood flow (RMBF) in an established ovine model of septic shock following severe smoke inhalation injury. Twenty-one sheep were randomized into a sham group (no injury), a control group (smoke/sepsis), and a treatment group (smoke/sepsis/WW-85; n=7 each). WW-85 was administered 1h post injury as bolus (0.1 mg/kg), followed by a continuous infusion of 0.02 mg/kg/h RMBF was analyzed using colored microspheres. All control animals developed a hypotensive, hyperdynamic circulation and increased plasma levels of nitrate/-nitrite (NOx). All hemodynamic variables and NOx levels were significantly improved in the treatment group. In visceral organs of controls, blood flow to trachea, ileum, and spleen significantly increased (p<0.05). Blood flow to kidneys and pancreas significantly decreased (p<0.05). Treatment with WW-85 stabilized blood flow to ileum, spleen, and kidneys on baseline levels and was significantly improved compared to controls (p<0.05). Cerebral blood flow deteriorated in controls, but was significantly improved in cerebral cortex, cerebellum, pons, medulla oblongata, and thalamus (p<0.05) by WW-85. These results provide evidence that WW-85 blocks NO production, thereby improving cardiovascular function and microcirculation.